(untitled) (Jurnal Simki Economic, 2025)
Through a case study of private college students in Jember City, this study aims to examine the influence of Gender, Financial Literacy, Hedonistic Lifestyle and Personality on personal financial management. The financial behavior of the community, especially the younger generation, is also influenced by these factors. Although most of their money is covered by their parents, students begin to be able to manage their finances independently when they enter adolescence and transition to adulthood. Someone who has a consumptive behavior tends to spend more money than they earn, and students tend to be interested in things that are trending or known as fomo. By using a quantitative research approach and a sample size of 100 respondents, a questionnaire was used to collect data, the population in this study were active students studying at PTS in Jember City. Based on the research results obtained from the use of the SPSS version 24 program and multiple linear regression analysis techniques, personal financial management is significantly and positively influenced by Gender, Hedonistic Lifestyle, Financial Literacy, and Personality. (Case Study of Private College Students in Jember City).